Sosialisasi Platform Berbasis Teknologi dalam Meningkatkan Pemahaman Dosen dan Mahasiswa terhadap Pembelajaran Bahasa Arab di Era Society 5.0 - Mahyudin Ritonga; Fauzul Fil Amri; Rahmat Linur; Khairul Fuadi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
The era of society 5.0 is a time when humans must be able to maximize technology in their every activity. Meanwhile, lecturers and students at STAIN Mandailing Natal are faced with a lack of understanding of the devices and platforms that can be used in learning Arabic. Therefore, this activity is intended to strengthen the understanding of lecturers and students on various platforms that can be used in learning Arabic in the era of society 5.0. The activity is carried out in the form of seminars, the implementation technique is carried out by presenting the material which is then continued with question and answer. Data is obtained through direct interaction with assisted participants. The interaction in question is the communication carried out by the resource person before and after the presentation of the material. In accordance with the results of the activity, it is known that assisted participants have an increased understanding of several platforms that can be used in learning Arabic. This conclusion is based on the presence of a positive response to the questions asked after the presentation of the material, besides that the enthusiasm of the participants to explore and study various platforms other than those that are socialized also grows after the implementation of the activity.